Mechanical properties and energy evolution characteristics of fissure sandstone under the interaction between water and fissures - Qingqing He; Jianhua Deng; Guixin Yuan (PLoS ONE, 2026)
To investigate the mechanical properties and damage evolution of fissure sandstone under the interaction between water and fissures, this study performed uniaxial compression tests on sandstone specimens with different water conditions (dry, natural, and saturated) and fissure angles (0°, 30°, 45°, 60°, and 90°). The experimental results indicate that peak strength decreased markedly with increasing water content, with reductions of 28.68%–53.99% under saturated conditions relative to dry conditions. In contrast, peak strength increased progressively with fissure angle. Crack initiation stress and crack damage stress exhibited similar trends. Based on the normalized ratios of characteristic stress, two damage evaluation indices, R c i and R c d , were proposed to characterize the weakening effect of fissures on rock bearing capacity during the crack initiation and crack propagation stages, respectively. The energy evolution results show that the strain energy corresponding to characteristic stress decreases significantly with increasing water content and generally increases with fissure angle. In addition, this study introduced a warning coefficient λ based on the ratio of elastic strain energy to dissipated strain energy to identify precursor information associated with rock failure. The results show that λ increased with water content and varied with fissure angle in an M-shaped pattern, with significant peaks at 30° and 60°. Under saturated conditions, water exerted the strongest effect on mechanical parameters at a fissure angle of 0°, while the overall effect remained relatively small at 30°. These findings provide a valuable reference for risk assessment and disaster prevention in geotechnical engineering.